Beyond history and "on a roll": The list of the most well‐studied human protein structures and overall trends in the protein data bank. (4th March 2021) - Li, Zhen‐lu; Buck, Matthias
Abstract: Of the roughly 20, 000 canonical human protein sequences, as of January 20, 2021, 7, 077 proteins have had their full or partial, medium‐ to high‐resolution structures determined by x‐ray crystallography or other methods. Which of these proteins dominate the protein data bank (the PDB) and why? In this paper, we list the 273 top human protein structures based on the number of their PDB entries. This set of proteins accounts for more than 40% of all available human PDB entries and represent past trends as well as current status for protein structural biology. We briefly discuss the relationship which some of the prominent protein structures have with protein research as a whole and mention their relevance to human diseases. The top‐10 soluble and membrane proteins are all well‐known (most of their first structures being deposited more than 30 years ago). Overall, there is no dramatic change in recent trends in the PDB. Remarkably, the number of structure depositions has grown nearly exponentially over the last 10 or more years (with a doubling time of 7 years for proteins, obtained from any organism). Growth in human protein structures is slightly faster (at 5.9 years). The information in this paper may be informative to senior scientists but also inspire researchers who are new to protein science, providing the year 2021 snap‐shot for the state of protein structural biology.